Understanding the challenges of deploying a milestone-tracking application in a cross-cultural context - Escobedo Bravo, Lizbeth Olivia; Arriaga, Rosa I. (My University)
Actively tracking children's developmental milestones can alert caregivers to possible developmental delays. However, this can be difficult since there are only a few resources that provide reliable and culturally sensitive references for tracking and logging developmental progress. To address this issue, we adapted the milestone-tracking mobile application of the Centers for Disease Control and Prevention for Mexican-Spanish-speaking individuals and called it ActEarlyMEX. We conducted both a usability study (including two culturally different cohorts) and a two-month deployment study to understand milestone-tracking behavior in the real world. The usability study helped us create a culturally relevant app that we evaluated in the deployment study, in which we recruited 24 participants (18 parents and 6 family members) from a local day care center. The results showed that ActEarlyMEX provided participants with insights into age-appropriate developmental milestones. The participants also indicated that multiple caregivers should be allowed to simultaneously use ActEarlyMEX and that there should be a feature that automatically updates relevant milestones based on a child's behavior. The results also provide insights for researchers that investigate culturally situated health informatics and define a set of design guidelines for studying milestone tracking. RESUMEN El seguimiento activo de los hitos del desarrollo de los niños puede alertar a los cuidadores sobre posibles retrasos en el desarrollo. Sin embargo, esto puede ser difícil ya que solo hay unos pocos recursos que brindan referencias confiables y culturalmente sensibles para rastrear y registrar el progreso del desarrollo. Para abordar este problema, adaptamos la aplicación móvil de seguimiento de hitos de los Centros para el Control y la Prevención de Enfermedades para personas de habla hispana mexicana y la llamamos ActEarlyMEX. Realizamos un estudio de usabilidad (que incluye dos cohortes culturalmente diferentes) y un estudio de implementación de dos meses para comprender el comportamiento de seguimiento de hitos en el mundo real. El estudio de usabilidad nos ayudó a crear una aplicación culturalmente relevante que evaluamos en el estudio de implementación, en el que reclutamos a 24 participantes (18 padres y 6 miembros de la familia) de una guardería local. Los resultados mostraron que ActEarlyMEX proporcionó a los participantes información sobre los hitos del desarrollo apropiados para la edad. Los participantes también indicaron que se debe permitir que varios cuidadores usen simultáneamente ActEarlyMEX y que debe haber una función que actualice automáticamente los hitos relevantes en función del comportamiento de un niño. Los resultados también brindan información para los investigadores que investigan la informática de la salud culturalmente situada y definen un conjunto de pautas de diseño para estudiar el seguimiento de hitos.
Interna onal Journal of Human-Computer Studies 162
Keywords: Developmental milestones; Mobile health; Parenting; Mobile app; Children; Milestone-tracking tool; Campus Tijuana